Environmental testing and characterization of fibre reinforced silica aerogel materials for Mars exploration. (December 2019) - Rocha, Helena; Lafont, Ugo; Semprimoschnig, Christopher
Abstract: Aerogels are promising materials for thermal insulation applications for Mars exploration mission. To assess the use of hydrophobic silica based aerogels for the specificity of the Mars environment, the samples were exposed to a laboratory simulation of the Mars environment, resorting to gamma radiation exposure and thermal cycling tests. To validate their use and study the effect of the simulated Mars environment on their thermal, mechanical and chemical properties, the aerogel materials were characterized before and after that environmental testing, to evaluate and identify eventual changes. Outgassing tests were also conducted. We found minor changes on the aerogels properties, showing that the materials can keep their thermal insulation performance after thermal cycling tests and that the storage modulus during dynamic mechanical analysis in compression mode was improved. Highlights: TGA after particle radiation show changed thermal stability of silica aerogels. DMA after particle radiation show increased storage modulus of silica aerogels. FTIR shows that silica aerogels are chemically stable towards particle radiation. There were no significant changes on thermal conductivity after thermal cycling. Thermal vacuum outgassing tests show that samples are compliant with requirements.